Russia’s Summit with ASEAN: Pivot to the East? - Dave, Bhavna (2016)
Russia is hosting a summit in Sochi on 19-20 May 2016 to commemorate twenty years of its dialogue relations with ASEAN. It will explore further cooperation between the two in another affirmation of Russia’s growing ‘pivot to the east’ policy under President Vladimir Putin, concurrent with its falling-out with the West. What are Russia’s objectives, its ‘Asian’ credentials and the potential for economic and strategic cooperation with ASEAN?